New strategies for economically feasible CO2 electroreduction using a porous membrane in zero-gap configuration. Issue 29 (19th July 2021) - Lee, Woong Hee; Kim, Kyeongsu; Lim, Chulwan; Ko, Young-Jin; Hwang, Yun Jeong; Min, Byoung Koun; Lee, Ung; Oh, Hyung-Suk
Abstract : Technoeconomic analysis (TEA) sensitivity results for a CO2 RR system with porous membrane (PM). Abstract : The high capital cost of electrolyzers is one of the major obstacles encountered in the industrial adoption of electrochemical CO2 reduction (CO2 R) systems. The anion exchange membrane (AEM) is a major contributor to the cost of electrolyzers. Herein, we propose a strategy for improving the economic feasibility by applying a low-cost porous membrane (PM). For a CO2 R reaction (CO2 RR), the activity and selectivity of an electrolyzer using a PM were found to be similar to those achieved using an AEM. Furthermore, the physical properties of PM, such as pore size, hydrophobicity, and thickness, can be tuned to suit the CO2 RR. A techno-economic analysis of the entire process revealed that adopting a PM is economically advantageous compared to adopting an AEM. Our results not only provide new practical and economical insights into the CO2 RR, but also demonstrate its potential extension to a variety of electrolytic systems.